2011
DOI: 10.1111/j.2044-8325.2010.02012.x
|View full text |Cite
|
Sign up to set email alerts
|

How changes in subjective general health predict future time perspective, and development and generativity motives over the lifespan

Abstract: In this study, we used the lifespan theories of selection optimization and compensation (SOC) and the socio‐emotional selectivity theory (SST) to integrate the disengagement and activity perspectives on aging and to explain intra‐individual changes in work motivation. A two‐wave longitudinal survey study was conducted among 600 Dutch university employees to test relations between intra‐individual changes in subjective general health, future time perspective (FTP), and generativity and development motives. In l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
151
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(183 citation statements)
references
References 54 publications
12
151
2
2
Order By: Relevance
“…Our results also extend previous findings by Kooij and Van De Voorde (2011) and others (e.g., Bal et al, 2010;Kooij et al, 2013) by showing the role of promotion focus in mediating the FTP -growth work motives relation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results also extend previous findings by Kooij and Van De Voorde (2011) and others (e.g., Bal et al, 2010;Kooij et al, 2013) by showing the role of promotion focus in mediating the FTP -growth work motives relation.…”
Section: Discussionsupporting
confidence: 91%
“…As such, the current study contributes to existing knowledge in two ways. First, building on Kooij and Van De Voorde (2011), who found that future time perspective (FTP) is positively associated with growth work motives, this study looks at the mechanisms by which FTP affects growth work motives. Specifically, based on the SOC model and literature (Baltes & Baltes, 1990), we examine the mediating role of promotion focus.…”
mentioning
confidence: 99%
“…Therefore, we also distinguish open-ended and limited FTP and we argue that, because of their differential effect on work motives (Carstensen, 1995;Kooij & Van de Voorde, 2011), open-ended and limited FTP are likely to evoke different forms of job crafting, which in turn will influence work engagement and job performance . More specifically, based on socio-emotional selectivity theory (SST) (Carstensen, 1995(Carstensen, , 2006, we argue that employees with an open-ended FTP focus on expanding their long-term breadth of knowledge and thus craft their job by increasing structural and social job resources and challenging job demands that are rewarding to them, whereas employees with a limited FTP focus on experiencing short-term positive emotions, and thus craft their job by decreasing hindering job demands that produce distress.…”
mentioning
confidence: 99%
“…Earlier studies distinguished open-ended FTP, referring to individuals' beliefs that they have an open-ended future time full of new goals, plans, and possibilities, and limited FTP, referring to individuals' beliefs that they have a limited future time characterized by constraints, restrictions, and limited possibilities (e.g., Cate & John, 2007;Kooij & Van de Voorde, 2011;Zacher & de Lange, 2011). Therefore, we also distinguish open-ended and limited FTP and we argue that, because of their differential effect on work motives (Carstensen, 1995;Kooij & Van de Voorde, 2011), open-ended and limited FTP are likely to evoke different forms of job crafting, which in turn will influence work engagement and job performance .…”
mentioning
confidence: 99%
See 1 more Smart Citation